The mediating role of coping between Alexithymia and mental health problems among women with PCOS - Khan, Rimsha; Bukhari, Syeda Razia (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Polycystic Ovarian Syndrome (PCOS) serves as a challenge for women globally, with a never-ending struggle with Alexithymia and mental health problems. To assess Alexithymia in women diagnosed with PCOS and the mediating effect of coping strategies emotion-focused coping (EFC), problem-focused coping (PFC), and dysfunctional coping (DC) between Alexithymia and mental health problems (anxiety, depression, behavior control, and positive affect) among women diagnosed with PCOS living in Islamabad, Pakistan. This mediation study was conducted in Islamabad. A hundred women with PCOS were approached for this study through various OB/Gynae clinics and fertility groups on social media. Participants completed the Perth Alexithymia Scale, Brief Cope Inventory, and Mental Health Inventory. The results suggest that significant mediation exists of EFC (p = .09) between Alexithymia and anxiety, EFC (p = .02) between Alexithymia and depression, EFC (p = .01) between alexithymia and behavior control in addition, significant mediation of EFC (p = .04) exists between Alexithymia and positive affect. Coping (EFC, PFC, and DC) partially mediates between Alexithymia and mental health problems (anxiety, depression, behavior control, and positive affect) among women diagnosed with PCOS. Further analysis suggests that DCS has a negative mediating effect between Alexithymia and mental health problems (M-anxiety = -.0465; p = .13, M-depression = -.0461; p < .01, M-behavior control = -.0431; p < .01 and M-positive affect = .0333; p = .02). The mediating result is significant for EFC between alexithymia and mental health problems whereas, PFC partially mediates and DC has a significant negative mediating effect between Alexithymia and mental health problems among women with PCOS.